Automation of normative money value of lands of settlements with the use of geoinformation technologies - Shulgan, Roman; Yanchuk, Oleksandr; Panchuk, Yuriy; Serilko, Dmytro (Geodesy and Cartography, 2023)
In this paper, the constituent elements of geoinformation support for the normative monetary valuation of the lands of settlements has been considered. A set of geospatial data necessary for land value of settlements at each of its stages has been formed. A method of economic and planning zoning based on the theory of fuzzy sets is proposed, namely the method of arranging objects according to a set of features, which allows applying real values of evaluation indicators and calculating their integral values. The algorithm of automated zoning with the use of GIS tools has been considered. Based on the proposed set of geospatial data, an ArcGIS tool was created using the Model Builder application, which allows you to determine the normative money value of a separate land plot and generate a report.